2005
DOI: 10.1021/jp0465940
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Properties of ZnS Nanoclusters

Abstract: Earlier studies have shown that the most stable structures for (ZnS)n clusters with n = 10-47 are hollow polyhedral clusters ("bubbles"). We report a detailed study of larger clusters, where n = 50, 60, 70, and 80, for which onionlike or "double bubble" structures are predicted. We report calculations of the vibrational spectra and the electronic structure of bubble and double bubble clusters, which may assist in their experimental identification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
122
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(146 citation statements)
references
References 37 publications
23
122
0
1
Order By: Relevance
“…[37][38][39][40][41][42][43][44][45] However, studies of the properties of endohedral compounds made of these hollow nanoclusters are scarce. Of particular relevance to the present research are the recent studies on the Mn@Zn 12 O 12 endohedral compound, [46] and on the endohedral compounds of the type…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[37][38][39][40][41][42][43][44][45] However, studies of the properties of endohedral compounds made of these hollow nanoclusters are scarce. Of particular relevance to the present research are the recent studies on the Mn@Zn 12 O 12 endohedral compound, [46] and on the endohedral compounds of the type…”
Section: Introductionmentioning
confidence: 99%
“…The structures of these hollow Zn i S i nanoclusters have been characterized in previous works. [38,41] These two semiconducting nanoclusters have been chosen because of their high symmetry and highly spheroidal shape, which allow for favored endohedral structures as compared to other nanoclusters, [30] rather than for their experimentally proven enhanced stability.…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticles have been modeled with bidimensional slabs of increasing thickness d (from 0.5 to about 6 nm), characterized by two infinite dimensions (x, y) and a finite thickness, and cut from the bulk so as to expose the most stable ZnS surface, the (110) [29]. Stoichiometric ZnS slabs (Zn/S ratio equal to 1/1) have been considered, in agreement with the experimental and theoretical reports [28,[48][49][50][51]. Surface Energy (E s ) is calculated as:…”
Section: Dft Modelingmentioning
confidence: 82%
“…In order to stick with the geometries considered for (MgO) 6 we only selected composites whose drumlike hexagonal cluster is the global minimum, in analogy to (MgO) 6 , or an isomer competitive in energy to the global minimum. These can be oxides (X = Mg, Ba, Be, Zn and Y = O), [42][43][44][45] selenides (X = Zn, Cd and Y = Se), 46 sulfides (X = Zn, Cd and Y = S), 46,47 halides (X = Na, Li and Y = F, I), 48,49 and the (BN) 6 nitride. 50 The geometry optimizations revealed that oxides are the most promising systems for hydrogen storage, with adsorption energies at the VWN level in the range of B0.3 to 0.4 eV, see adsorption energy values in Table S2 of the ESI.…”
Section: Computational Modelsmentioning
confidence: 99%